A Study of Online Information Search and Experience Goods from Travel and Tourism Perspective - Tsai, Chih-CHien (2009)
This study investigated consumer behaviour in online travel information search. Based on Engel-Kollat-Blackwell Model, ATR and TAM theory, the study was designed to discover similarities and differences between European and Asian students in pre-purchase, purchase and post-purchase stages. The study was conducted by qualitative research; a semi-structured interview was selected to be the research method, in order to unearth more detailed data through flexible conversation. According to the findings, European and Asian students have similar perspectives on the six selected determinants influencing the attitude towards the use of the Internet, including the perceived usefulness, the perceived ease of use, previous experience, others’ opinions, online security and inconsistency. Besides, the students in both groups are proved to have a repeating search habit. Despite the similarities, students from Europe and Asia have different travel information sources and searching purposes. While Asian students tend to use online travel information for a specific trip, European search for the information not only for trips but also for fun and social. Asian students also use guide books as alternative sources more often. In addition, Asian students may encounter more difficulties than their European counterparts due to the deficiency in the language backgrounds.